The Dynamic Impact of Crude Oil Price and Real Estate Growth on Stock Market Performance - Yau, Josephine Tan Hwang; Awang Omar, Dayang Siti Salbiah binti; Khan, Mubashir Ali; Liwan, Audrey; Kueh, Jerome Swee Hui (Society of Business and management, 2021)
This paper examines the effect of crude oil price and real estate growth on Malaysian stock market performance by examining the monthly data from 1999-2016 using both linear and non-linear tests. These tests examine the long-run and short-run relationship among variables. Granger causality test is used to measure the short-run adjustments towards the long-run relationship among the variables. The results of Granger causality test indicates that a bidirectional relationship exists between stock market performance, crude oil price, real estate. In other words, there is a dynamic relationship among the stock market performance, crude oil and real estate.